Tailoring Multifunctional Small Molecular Photosensitizers to In Vivo Self‐Assemble with Albumin to Boost Tumor‐Preferential Accumulation, NIR Imaging, and Photodynamic/Photothermal/Immunotherapy (Small 27/2022). Issue 27 (7th July 2022) - Luo, Shenglin; Luo, Xi; Wang, Xiaojiao; Li, Lian; Liu, Huiguo; Mo, Banghui; Gan, Hongbo; Sun, Wei; Wang, Liting; Liang, Houjie; Yu, Songtao
Abstract : Cancer Immunotherapy In article number 2201298, Houjie Liang, Songtao Yu, and co‐workers report how localized cancer phototherapy on primary tumors with nanosized small molecule‐albumin complexes by in vivo self‐assembly, ultimately trigger sufficient antitumor immune responses to effectively suppress growths of distant metastatic tumors.